Mengembangkan Bahan Ajar Mata Kuliah Permodalan Koperasi Untuk Meningkatkan Motivasi dan Hasil Belajar Mahasiswa - Ekawarna, Ekawarna (UI Scholars Hub, 2007)
The objective of this study is to develop ‘Buku Ajar Permodalan Koperasi” and describe the effectivity of that textbook in student learning motivation and student learning achievement. The textbook has been developed using the Four-D model of Thiagarajan et al, 1974, that include phase of define, design, develop, and disseminate. The textbook consist of six chapter based on Atwi Suparman model (Panen and Purwanto, 2001). Result from this classroom action research shows that the textbook can develop student learning motivation and also student academic achievement.